CONTRIBUTION OF SITI WALIDAH IN THE NATION CHARACTER BUILDING THROUGH ‘AISYIYAH MOVEMENT - Cahyaningrum, Lingga Wisma; Jamuin, Ma?arif (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
Siti Walidah is a reformer, the founder of ?Aisyiyah, and also promoter of the nation character building. Her contribution in the efforts to establish the nation character has been manifested in formal and informal education, and social movement since 1918. She also did a breakthrough in her era by setting up ?Aisyiyah along with its various activities, particularly the initiative in providing Islamic education for women. The movement is guided by the Quran and Sunnah in the framework of the nation character building with Prophet Muhammad as the role model. The guideline of the movement is beautifully reflected in ?Aisyiyah Mars, which is still amendable until now.